De Psalmist als Hizkia, zoon van David. Een intertextuele lezing van Psalm 138 en Jesaja 36-38 - Beuken, Wim (Verbum et ecclesia, 1998)
The Psalmist as Hezekiah, Son of David. An Intertextual Reading of Psalm 138 and Isaiah 36-38: Recent research into the Psalms has shown that the 'I' of the laments and the psalms of praise should not be explained in biographical or functional programmatic (cult or court) terms, but should be viewed rather as a metaindividual and paradigmatic figure. Thus the psalmist of one psalm is akin to that of another, their ego being formed according to literary norms. This insight justifies an intertextual reading of the psalms and other biblical texts. Against the background of 2 Chr 32:25, in which Hezekian is accused of ingratitude, the present study endeavours to show that Psalm 138, a song with royal characteristics, can be read as a song of thanksgiving and placed on the lips of Hezekiah. Semantic correspondences with Isaiah 36-38 are both strong and persuasive.